INTAXMOD: Inheritance and gift taxation in the context of ageing - Alexander Krenek; Margit Schratzenstaller; Klaus Grünberger; Andreas Thiemann (European Commission, Joint Research Centre (JRC), 2022)
Based on the most recent data from the ECB's Household Finance and Consumption Survey, the project models the future household-level wealth distribution in five selected EU member countries (Finland, France, Germany, Ireland, and Italy) to derive inheritances based on different demographic and wealth projection scenarios. On this basis, various inheritance tax scenarios are simulated to estimate potential inheritance tax revenues for a projection period of 30 years. Our results indicate that multiple factors coincide in favouring a growing revenue potential for inheritance taxation in the medium-term. Wealth accumulation and appreciation lead to higher average wealth levels. The shift of the baby boomer generation out of the labour force results in an increase of the older population both in absolute and relative terms. Eventually, this will lead to a rise in the number of deaths and the number of inheritances. Additionally, low fertility rates lead to a reduction of the average number of successors and thereby decrease the importance of exemption thresholds, as individual inheritances become larger. Overall, our simulations show that the future revenue potential of inheritance taxes may be substantial. In practice, it can be expected that the theoretical revenue potential demonstrated by our simulations will be reduced by tax avoidance, real responses, and general equilibrium effects on other taxes. A review of the empirical evidence shows that behavioural responses to inheritance taxes are less pronounced compared to a net wealth tax.
Keywords: H24; H3; 330; inheritance taxation; wealth taxation; ageing; HFCS; behavioural effects